1987
DOI: 10.3109/00016348709083041
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Retinal Hemorrhages and Neurobehavior Related to Tractive Force in Vacuum Extraction

Abstract: Fifty clinically indicated vacuum extractions were studied to evaluate a possible relationship between neurobehavioral abnormality, retinal hemorrhages and the tractive force used for delivery. A Vacuum Extractor Recorder (Type SF 30, Knick), was used to measure the forces necessary for delivery of the head. Infants delivered by the use of extensive tractive force showed no greater incidence of neuropathology than those delivered with less tractive force. The retinal hemorrhages were equally distributed among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Considering the prevalence, characteristics, and risk factors of RH is important for disease management. Previous studies based on non-neonatal digital wide-field fundus imaging systems have been conducted [ 1 , 4 , 6 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Emerson investigated the prevalence and disappearance rate of retinal hemorrhage in 149 healthy neonates using indirect ophthalmoscopy and found that 34% of the subjects had retinal hemorrhage of varying severity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the prevalence, characteristics, and risk factors of RH is important for disease management. Previous studies based on non-neonatal digital wide-field fundus imaging systems have been conducted [ 1 , 4 , 6 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Emerson investigated the prevalence and disappearance rate of retinal hemorrhage in 149 healthy neonates using indirect ophthalmoscopy and found that 34% of the subjects had retinal hemorrhage of varying severity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, as described in postmortem experiments, the actual detachment situation may offer a possible pathological pathway in and of itself 31 . Svenningsen 18,26 and Vacca 21 used retinal hemorrhage and cephalohematoma, respectively, as neonatal outcome but did not find any (significant) association with traction force. Saling described possible cases of morbidity induced by traction force but did not attempt a quantitative analysis 17 …”
Section: Discussionmentioning
confidence: 98%
“…Studies embracing these approaches have reached different conclusions regarding the effect of mode of delivery. 3,[15][16][17][18] There is no evidence-based traction force safety limit, and since previous studies have observed peak traction forces of up to 452 Newton using a metal cup, the notion of a self-limited traction force maximum (theoretically negative pressure × area of the cup) before detachment seems unreliable. 19,20 For rigid plastic cups, the maximum peak traction force is considerably lower than for metal cups, at less than 11.5 kg (113 Newton [N]) in 80% of cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auch Hirnblutungen und Retinablutungen sind hfiufig nach vaginal-operatiyen Entbindungen zu beobachten (Bahgat 1987, Egge et al 1981 1984, O'Leary et al 1986, Svenningsen und Eidal 1988, Svenningsen et al 1987, van Zundert et al 1986 (Svenningsen und Eidal 1988). Die VorsteUung fiber die Blutungsentstehung geht davon aus, dab konstanter Druck auf den fetalen Sch/idel zur Odembildung und damit zu erh6htem intrakranialen Druck mit Stase in den Retinavenen ftihre ).…”
Section: Ungiinstige Eigenschaften Der Periduralangisthesieunclassified